2022
DOI: 10.3390/biology11010062
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cranial Orientation on Forensic Frontal Sinus Identification as Assessed by Outline Analyses

Abstract: The utility of frontal sinuses for personal identification is widely recognized, but potential factors affecting its reliability remain uncertain. Deviations in cranial position between antemortem and postmortem radiographs may affect sinus appearance. This study investigates how slight deviations in orientations affect sinus size and outline shape and potentially impact identification. Frontal sinus models were created from CT scans of 21 individuals and digitally oriented to represent three clinically releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 62 publications
(127 reference statements)
0
7
1
Order By: Relevance
“…However, clearly rotated skulls that would produce distorted outlines and measurements were removed prior to analysis. While Butaric et al [ 47 ] found that 5% deviations in CT skull orientation did not dramatically impact subsequent sinus outlines, measurements, or positive matches, minor inter-individual deviations in head position may have minimally impacted the results presented here. Additionally, a very slight error may have been introduced during the manually digitized tracing of the CT image slices.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…However, clearly rotated skulls that would produce distorted outlines and measurements were removed prior to analysis. While Butaric et al [ 47 ] found that 5% deviations in CT skull orientation did not dramatically impact subsequent sinus outlines, measurements, or positive matches, minor inter-individual deviations in head position may have minimally impacted the results presented here. Additionally, a very slight error may have been introduced during the manually digitized tracing of the CT image slices.…”
Section: Discussioncontrasting
confidence: 53%
“…This study used clinically derived cranial CT scans that were not necessarily oriented on the anthropologically preferred Frankfurt Horizonal Plane [ 22 , 47 ]. However, clearly rotated skulls that would produce distorted outlines and measurements were removed prior to analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ancestry is not listed, the samples are likely largely composed of European-American individuals. Radiographs and frontal sinus outlines (see details below) were previously collected for larger, ongoing studies of frontal sinus morphology and identification methods, e.g., [ 25 , 26 ]. The sample included ten outlines which were randomly selected in R from 244 possible sinus outlines on 128 adult individuals used in a previous study (note: some individuals had several radiographs at different age points, explaining the higher number of outlines versus individuals) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Within the realm of individualizing factors, Butaric, Richman, and Garvin [ 5 ] discuss the potential factors that might affect the reliability of using frontal sinuses for personal identification. Their study investigates how slight deviations in orientations affect sinus size and outline shape, which could potentially impact identification.…”
mentioning
confidence: 99%